Influence of Phyllanthus niruri Linn. Extract Therapy on Renal and Uterus in 2% NaCl -induced Fibrotic Scarring Rodents - Khairil Pahmi; Lale Syifaun Nufus; Dahlia Andayani (Fakultas Ilmu Kesehatan UNW Mataram, 2023)
Background Phyllanthus niruri (english name : leafflower) extract is used in therapy of renal and uterus fibrotic scarring disease. Influence of alcohol extract of P. niruri on renal and uterus of 2% NaCl- induced fibrotic scarring rodents had been researched. Aim of Study Purpose of this research to study the influence of leafflower (Phyllanthus niruri Linn.) therapy on renal and uterus in 2% NaCl - induced fibrotic scarring rodents. Methods Wistar rodents were stimulated with 2% NaCl in drinking water to induce fibrotic scarring renal and uterus. Phyllanthus niruri extract (200 mg/kg) was given orally for 4 weeks. Matrix extracellular expression was determined by HE Staining and calculated by METAVIR fibrosis scarring score. The data of this study were analyzed by SPSS 16. Results niruri extract was able to decrease the matrix extracellular in 2% NaCl-induced rodent compared to control group (p<0.05). Conclusion P. niruri extract was able to decrease the matrix extracellular in the renal and uterus of the rodents.